Determination of Competence, Service Excellen, And Application of System Management Information on the Performance of District Employees in Karimun Regency Through Job Satisfaction as an Intervening Variable - LIHARYANTI, Uci; NGALIMAN, Ngaliman; YANTI, Sri (Journal of Governance, Taxation and Auditing, 2025)
The performance achievement of employees in the Karimun Regency Districts was not achieved according to the target, due to employee dissatisfaction, competence, excellent service and the application of management information systems. This mixed-method study aimed to determine the role of job satisfaction on competence, excellent service and the application of management information systems on employee performance. It was concluded that competence and positive job satisfaction significantly determine employee performance. Excellent service and the application of management information systems do not significantly determine employee performance. Furthermore, competence, excellent service and the application of management information systems positively and significantly determine job satisfaction. Then job satisfaction is able to intervene positively significantly with perfect determination of competence, excellent service and the application of management information systems on employee performance. This means that competence and satisfaction have a significant impact on employee performance. At the same time, excellent service and the application of management information systems have not had a significant impact. Furthermore, competence, excellent service and the application of management information systems have a significant impact on job satisfaction. Then job satisfaction can perfectly strengthen the influence of excellent service and the application of management information systems on employee performance, but competence can be partially strengthened.